Competition, Adverse Selection, and Information Dispersion in the Banking Industry: Table 1 - Marquez, Robert (Review of Financial Studies, 2002)
Proprietary information generated through the process of lending can impact the structure of the banking industry. With more competing banks, borrower-specific information becomes more disperse, as each bank becomes informed about a smaller pool of borrowers. This reduces banks’ screening ability, creating an inefficiency as more low-quality borrowers obtain financing. Incumbent banks’ information advantage may also create difficulties for potential entrants, so that entry should be easier in markets with high borrower turnover or where entrants have specific expertise in evaluating credit risks. We draw implications for whether financial deregulation is likely to increase borrowers’ surplus, and what patterns of entry might be observed.